Valori di Mmax, di b, completezze. Dati di ingresso per la redazione di MPS04 - Stucchi, Massimiliano; Meletti, Carlo; Montaldo, Valentina; Akinci, Aybige; Faccioli, Ezio; Gasperini, Paolo; Malagnini, Luca; Valensise, Gianluca (Istituto Nazionale di Geofisica e Vulcanologia (INGV), 2004)
The dataset contains some parameters assessed for the computation of the MPS04 seismic hazard model of Italy. The file contains 3 sheets:
i) Mmax values (and relevant seismicity rates when Mmax is higher than observations) and b values for each seismic source zone;
ii) Completeness intervals estimated with an approach prevalently historical;
iii) Completeness intervals estimated with an approach prevalently statistical.

Il dataset contiene alcuni parametri utilizzati per il calcolo dei valori di pericolosità sismica MPS04. Il file si compone di tre fogli excel:
i) valori di Mmax e relativi tassi (solo nei casi in cui Mwmax non corrisponde al valore osservato), valori di b;
ii) intervalli di completezza prevalentemente storici (CO-04.2);
iii) intervalli di completezza prevalentemente statistici (CO-04.4).
Mmax, b value, and completeness of the seismic catalogue. Input data used for the compilation of MPS04
MPS04 Mmax
Keywords: maximum magnitude; intervals of completeness